Pengaruh Komitmen Tugas Pimpinan Perusahaan dan Budaya Organisasi Karyawan terhadap Efektivitas Kerja Karyawan pada CV Trikarsa Utama - Agung Prasetyo (Reslaj : Religion Education Social Laa Roiba Journal, 2020)
This study aims to reveal the influence of the Commitment of Corporate Leadership (X1) and organizational culture (X2) to the effectiveness of employee work (Y). The research method used was a survey method. The sampling technique uses stratified random sampling. The research sample amounted to 48 respondents. The trial results of the research instruments show that the reliability of the Likert scale instrument of organizational culture is 0.917, work motivation is 0.792, and work effectiveness is 0.854. Analysis of the data used is regression analysis. The conclusion of the research results revealed: (1) There is an influence of the Commitment of the Leadership of the Company to the effectiveness of the work of employees. From the analysis results obtained a regression coefficient of 3,336 means that the influence of the Commitment of the Leadership of the Company amounted to 33.36%. (2) There is a positive influence of organizational culture on work effectiveness. From the analysis results obtained a correlation coefficient of 3742 means that there is a positive influence of organizational culture on work effectiveness by 37.42%. (3) There is a positive influence of the Commitment of the Company's Leadership Tasks and organizational culture together on work effectiveness. From the results of the analysis obtained a regression value of 14.58 means that there is a positive influence on the Commitment of the Leadership of the Company and organizational culture together on work effectiveness is 14.58%. Keywords: leadership commitment, organizational culture, work effectiveness, employees